# calc

posted by .

find the derivatives of the given functions.
g(t)=sqrt t(1+t)/t^2

• calc -

Is that √ everything, or
√(t(1+t)) / t^2, or
(√t)(1+t)/t^2 ?

• calc -

Ah, I see from a prior post, we have

g(t) = √t (1+t)/t^2

you can expand that to be

g(t) = t^(-3/2) + t^(-1/2)
so the derivative is trivial:
g'(t) = -3/2 t^(-5/2) - 1/2 t^(-3/2)
= -(3+t) / (t^2 √t)

or you can use the product rule to get

g'(t) = 1/2√t (1+t)/t^2 + √t (1)/t^2 - 2√t (1+t)/t^3
= (1+t)/2t^2√t + 2t/2t^2√t - (4+4t)/2t^2√t
= (1+t+2t-4-4t)/2t^2√t
= -(3+t)/2t^2√t

• calc - find the typo -

find the typo so the two solutions agree!

• calc -

agree thank you steve

## Similar Questions

1. ### calc

Verify that the function satisfies the three hypotheses of Rolle's Therorem on the given interval. Then find all numbers c that satisfy the conclusiton of Rolle's Theorem. f(x)= x*sqrt(x+6) [-6,0] f is continuous and differential f(-6) …
2. ### math-Inverse functions

f(x)=-4x-2 & g(x)=5x-6. Find (f*g) and state domain. f(x)-x^2-1 what is the equation for f^-1(x)?
3. ### Calc

Can anyone help me find the derivative of these functions?
4. ### Calc

Find an expression for the function whose graph is the given curve. The top half of the circle x^2 + (y-2)^2 = 4 My final answer is y= 2 +/- sqrt of x-4 However, I circled the positive sign because that's the top half. Is this right?
5. ### calc

Find the derivatives of the following functions using the differentiation rules. f(x)=(x^3-2x^2+x+1)(sqrt(x)-3x+9) I did: f'(x)=[x^3-2x^2+x+1][(1/2x^(-1/2)-3]+[x^(1/2)-3x+9][3x^2-4x+1] which I got to be [-12x^3+(7/2)x^(5/2)+46x^2-5x^(3/2)-42x+(3/2)x^(1/2)+6]/[2x^(1/2)] …
6. ### Calc 2

How to find Cross Section Area given x=5 x=-5 y= sqrt(25-x^2) y= -sqrt(25-x^2)
7. ### Calculus

find the derivatives of the given functions. g(t)=sqrt t(1+t)/t^2 the sqrt is just over t.
8. ### Calculus

Find the outside and inside functions of the following to find their derivatives: 1) sqrt(2x+9) 2) cos(cos(x)) 3) tan(x) I already know how to find their derivatives I'm just not exactly sure what parts of the chain rule equation would …
9. ### Calculus

Find the sum and difference functions f + g and f – g for the functions given. f(x) = 2x + 6 and g(x) = 2x - 6 f(x) = x^2 - x and g(x) = -3x + 1 f(x) = 3x^3 - 4 and g(x) = -x^2 + 3 State the domain and range for the sum and difference …